Neoplastic Transformation-Associated Stimulation of the In Vitro Resolution of Concatemer Junction Fragments from Minute Virus of Mice DNA - Kuntz-Simon, Gaëlle (American Society for Microbiology, 1999)
Minute virus of mice (MVM) shows an oncotropic behavior reflected by its ability to amplify its genome more efficiently in a number of transformed versus normal cells. In vivo and in vitro studies revealed that the major effect of cell transformation on MVM DNA replication occurs at the level of double-stranded replicative-form amplification. In particular, resolution of MVM DNA concatemers into monomers was found to be highly sensitive to neoplastic transformation.